FAMILY FIRM PERFORMANCE OVER THE BUSINESS CYCLE: A META-ANALYSIS - Christopher Hansen; Joern Block; Matthias Neuenkirch (Journal of Economic Surveys, 2020)
The financial performance of family firms has been widely studied in the literature. Combining the results of 155 primary studies from 35 countries with data about business cycles, we investigate how family firm performance changes over the business cycle. Using meta-analytic estimation methods, we find that family firms outperform nonfamily firms in developed markets, irrespective of economic circumstances. This outperformance, although statistically significant, is very small and practically negligible. With regard to the business cycle, we find evidence for a procyclical effect in which the relative performance of family firms is lower in economically difficult times. Our study extends the literature on how family firm performance depends on macroeconomic factors.
Keywords: 330; Business cycle; Family firms; Financial performance; Meta-analysis